New lance lacewings (Osmylidae: Kempyninae) from the Middle Jurassic of Inner Mongolia, China - Ma, Yiming; Shih, Chungkun; Ren, Dong; Wang, Yongjie (Zootaxa, 2020)
Contrary to the typical southern distribution of the extant Kempyninae, a subfamily of Osmylidae, its fossil group shows the high diversification in the northern hemisphere during the Mesozoic. Herein a new genus with a new species, Mirokempynus profundobifurcus gen. et sp. nov., and a new species, Jurakempynus loculosus sp. nov., of Kempyninae, are described from the Middle Jurassic Jiulongshan Formation of Daohugou Village, Inner Mongolia, China. The new species share the characteristic synapomorphies of Kempyninae, e.g. subcostal veinlets mostly irregularly forked in the forewing and the distinctly expanded intramedial area with multiple rows of cells in the hind wing. The new genus distinctly shows a particular condition of intramedial area and MP branching in the hind wing. However, the condition of the region between MA and MP significantly broadened in the hind wing appear distinctively different to other known kempynine genera. A key is provided for all the genera of documented kempynines, both fossil and extant.